2015
DOI: 10.1038/srep09962
|View full text |Cite|
|
Sign up to set email alerts
|

A Novel Audiovisual Brain-Computer Interface and Its Application in Awareness Detection

Abstract: Currently, detecting awareness in patients with disorders of consciousness (DOC) is a challenging task, which is commonly addressed through behavioral observation scales such as the JFK Coma Recovery Scale-Revised. Brain-computer interfaces (BCIs) provide an alternative approach to detect awareness in patients with DOC. However, these patients have a much lower capability of using BCIs compared to healthy individuals. This study proposed a novel BCI using temporally, spatially, and semantically congruent audio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 51 publications
3
33
2
Order By: Relevance
“…Previous studies mainly focused on using BCI to detect the awareness of DOC patients [13][14][15]. These studies determined whether patients were aware by verifying whether the patients followed commands.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies mainly focused on using BCI to detect the awareness of DOC patients [13][14][15]. These studies determined whether patients were aware by verifying whether the patients followed commands.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study [15], we proposed an audiovisual BCI system for awareness detection in patients with DOC based on semantically congruent audiovisual stimuli, including visual and spoken numbers. Our experimental results for healthy subjects showed that the audiovisual BCI outperformed the corresponding visual-only and auditory-only BCIs, whereas the experimental results for the patients demonstrated satisfactory performance of the system in awareness detection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations